Ultrafast Charge‐Discharge Capable and Long‐Life Na3.9Mn0.95Zr0.05V(PO4)3/C Cathode Material for Advanced Sodium‐Ion Batteries. Issue 17 (1st February 2023) - Wang, Zhuangzhou; Cui, Guijia; Zheng, Qinfeng; Ren, Xiangyu; Yang, Qingheng; Yuan, Siqi; Bao, Xu; Shu, Chaojiu; Zhang, Yixiao; Li, Linsen; He, Yu‐Shi; Chen, Liwei; et al.
Abstract: Na4 MnV(PO4 )3 /C (NMVP) has been considered an attractive cathode for sodium‐ion batteries with higher working voltage and lower cost than Na3 V2 (PO4 )3 /C. However, the poor intrinsic electronic conductivity and Jahn–Teller distortion caused by Mn 3+ inhibit its practical application. In this work, the remarkable effects of Zr‐substitution on prompting electronic and Na‐ion conductivity and also structural stabilization are reported. The optimized Na3.9 Mn0.95 Zr0.05 V(PO4 )3 /C sample shows ultrafast charge‐discharge capability with discharge capacities of 108.8, 103.1, 99.1, and 88.0 mAh g −1 at 0.2, 1, 20, and 50 C, respectively, which is the best result for cation substituted NMVP samples reported so far. This sample also shows excellent cycling stability with a capacity retention of 81.2% at 1 C after 500 cycles. XRD analyses confirm the introduction of Zr into the lattice structure which expands the lattice volume and facilitates the Na + diffusion. First‐principle calculation indicates that Zr modification reduces the band gap energy and leads to increased electronic conductivity. In situ XRD analyses confirm the same structure evolution mechanism of the Zr‐modified sample as pristine NMVP, however the strong ZrO bond obviously stabilizes the structure framework that ensures long‐term cycling stability. Abstract : Zr‐substitution greatly enhances the electronic conductivity and Na + mobility of NASICON‐type Na4 MnV(PO4 )3 /C. The optimized Na3.9 Mn0.95 Zr0.05 V(PO4 )3 /C exhibit the best rate performance among the so far reported cation substituted Na4 MnV(PO4 )3 /C cathodes. The Na3.9 Mn0.95 Zr0.05 V(PO4 )3 /C cathode also shows excellent cycling stability.